SIFAT FISIK MINYAK SAWIT KASAR DAN KORELASINYA DENGAN ATRIBUT MUTU [Physical Properties of Crude Palm Oil and Their Correlations to the Quality Attributes] - Nur Wulandari; Tien R. Muchtadi; Slamet Budijanto; Sugiyono . (Jurnal Teknologi dan Industri Pangan, 2011)
Indonesia is the largest producer and exporter of crude palm oil (CPO) in the world. Process engineering applications of CPO during handling, transporting, and processing, need baseline data related to CPO’s physical properties. This research was aimed to obtain baseline data about physical properties of CPO and to study the correlation between CPO’s quality attributes to their physical property parameters. Study on physical property and quality of CPO was conducted to five CPO samples from different CPO’s producers. Those samples had variations on physical property parameters and quality attributes. Some physical property parameters of CPO were depended on the temperature of measurements. CPO samples showed non-Newtonian pseudoplastic behaviour at 25°C with various flow behaviour index (n) and concistency index (K), other wise at 55°C all CPO samples showed Newtonian behaviour.There were good correlations between quality attributes of CPO to their physical property parameters at 25°C, including correlations between free fatty acid contents of CPO and the temperatures of crystallization, as well as between iodine values and the rheological properties of CPO.